Does Job Satisfaction Rise and Fall with the Economy? Cross-Sectional, Longitudinal, and Experimental Evidence That Job Satisfaction Increases during Recessions - Bianchi, Emily C.; Martin, Chris C.; Li, Ren (Academy of Management Journal, 2023)
While recessions negatively influence many aspects of working life, we propose that they will positively affect job satisfaction. We argue that during bad economic times, alternative jobs will be less salient, and people will regard their own jobs as more satisfying. We test these predictions in three studies. Study 1 (N = 23,335) utilizes a large cross-sectional survey of American adults collected over four decades and finds that job satisfaction rises during recessions and falls during booms. Study 2 (N = 12,859) replicates this result using a large longitudinal survey of British adults and finds that job satisfaction rises and falls with the economy, even within the same people. Finally, Study 3 (N = 512) uses an experimental design and finds that when the economy falters, alternative jobs become less salient, which mediates the relationship between economic conditions and job satisfaction. While past work has shown that job satisfaction is influenced by situations within organizations, the current findings suggest that conditions outside of organizations can also shape how people affectively evaluate their jobs.